Out of the Middle East the emergence of an Arab global business - Shair, Kamal A. (I.B.Tauris & Co Ltd, 2016)
Shair was born in a small town in what was then Transjordan and dragged himself through school, moved to college in Beirut, then sailed off to America and returned to the Middle East to create a multinational corporate empire. Dar al Handasah was founded in a flat in Beirut and in contemporary times, spans the globe with offices in 37 countries